EKSTRAKSI DAN DETEKSI KANDUNGAN FITOKIMIA DAUN SALAM (Syzygium polyanthum) - Lestari, Devi Eka; Indriyani; Susanti, Nida Lidya (BIOMA : JURNAL BIOLOGI MAKASSAR, 2025)
Bay leaf (Syzygium polyanthum (Wight) Walp.) is one of the commonly used spices in cooking, known for enhancing the taste and aroma of food as well as offering health benefits. This study aims to identify the phytochemical content of bay leaves. The extraction method employed was maceration using 96% ethanol. The bay leaves were dried through aeration until the moisture content reached below 10%. The dried samples were then homogenized using a homogenizer to obtain a fine powder. The resulting powder was macerated with 96% ethanol. The obtained extract was then qualitatively tested for its phytochemical contents, including alkaloids, saponins, steroids, flavonoids, terpenoids, tannins, and phenolics. The results showed positive reactions for alkaloids with three reagents (Mayer, Boucardon, and Dragendorff), indicated by the formation of white, orange, and brown precipitates. Flavonoids were detected by a yellowish-green color change, while saponins produced stable foam. Tannins, steroids, and phenolics showed a dark green coloration, indicating the presence of these compounds. In contrast, the test for terpenoids yielded negative results. These findings indicate that bay leaf extract contains various secondary metabolites with potential antioxidant, antimicrobial, and other pharmacological activities. Keywords: Extraction, Phytochemical Detection, Bay Leaf